Experimental Strength Analysis of Variable Stiffness Waffel-Grid Cylindrical Compartments. Part 1. Experimental Procedure - Degtyarev, M.A.; Danchenko, V.G.; Shapoval, A.V.; Avramov, K.V. (Проблеми машинобудування, 2019)
This paper proposes a method of the experimental study of the static stress-strain state (SSS) of the variable stiffness tail section of a launch vehicle (LV). The article summarizes the results of the experimental analysis of the static SSS of an optimized tail section body under the conditions of loading close to realistic ones.